Gender-specific differences in white matter microstructure in healthy adults exposed to mild stress. (2nd January 2020) - Poletti, Sara; Melloni, Elisa; Mazza, Elena; Vai, Benedetta; Benedetti, Francesco
Abstract: Stress is a powerful moderator of brain plasticity and may affect several physiological functions such as the endocrine and the immune system. The impact of stress can be protective or detrimental according to several factors such as level of the stressor and age of occurrence. Also, the impact may differ in males and females. We aim to analyze the effect of mild levels of early and recent stress on white matter microstructure in healthy volunteers. MRI acquisition of diffusion tensor images with a 3.0 T scanner was performed on 130 healthy subjects (71 males and 59 females). Severity of early and recent stress was rated, respectively, on the Risky Families Questionnaire and on the Schedule of Recent Experiences; subjects were divided into low stress and mild stress groups. Mild early stress associated with lower fractional anisotropy (FA) in the cingulate gyrus compared to low early stress. Females reported reduced FA compared to males in the low-stress group in the internal capsule, posterior corona radiata, posterior thalamic radiation, superior longitudinal fasciculus, and sagittal stratum whereas no difference was observed in the mild stress group. An additive effect of early and recent stress was observed in posterior corona radiata, retrolenticular part of the internal capsule, and superior longitudinal fasciculus. The impact of early stress on WM microstructure in healthy subjects is different in males and females. While males seem to be more sensitive to early stress, an additive effect of early and recent stress manifests itself in females. Layman summary: Mild levels of early stress associate with lower white matter integrity measured by fractional anisotropy. Females and males show differences in white matter integrity when exposed to low levels of early stress with females showing lower white matter integrity compared to males. No difference in white matter integrity was observed for males and females exposed to mild levels of stress. Mild stress in females is associated with higher white matter integrity. Males seem to be more sensitive to early stress while females are more affected when early stress is followed by stress in adult life.